Perceptions of police use of force among U.S. adults and the role of communication accommodation in improving police–civilian interactions. Issue 6 (2nd November 2021) - Italiano, Rachel; Ramirez, Fanny; Chattopadhyay, Sumana
ABSTRACT: This paper examines how U.S. adults define police use-of-force and what these understandings of police violence mean for police–civilian interactions. Our findings show that public attitude is split between pro- and anti-law enforcement stances. Pro-law enforcement individuals see use-of-force as something that is part of the job for police officers, associate the term with positive emotions, and give the benefit of the doubt to police officers while engaging in victim blaming. Anti-law enforcement individuals associate the term with negative emotions, weapon imagery, injustice, racial bias, abuse of power, and harm or death. Young, democratic-leaning, lower socio-economic status individuals with prior police contact are most likely to express anti-law enforcement attitudes. Using communication accommodation theory, we recommend police officers adapt their communication to be more accommodating to the needs, concerns, and fears of civilians, particularly marginalized individuals. This approach may help create more accommodating, less violent police–civilian interactions.